جدلية الفصل والوصل بين الدين والعلم في الفكر الغربي: المثالية الألمانية أنموذجا - عبدالنور، محمد (مركز نماء للبحوث والدراسات, 2017)
حاول المقال استكشاف حقيقة سعي العلم الحديث إلى القيام مقام الدين ومدى تمكّنه من تحقيق ذلك، فكان العلم الحديث خاصة في نسخته التجريبية واضحا في منافسته للعقائد الدينية المدرسية السائدة خال العصور الوسطى في أوروبا، إذ إنه خالفها أساسا من حيث المنهج، فكان التقابل واضحا بين طريقة عقلية منطقية تعتمد الثقة في مقولات الأقدمين، وبين طريقة تجريبية لا تثق إلا في الحواس، تتخذ من الملاحظة والتجربة العلمية المصدر الوحيد للحقيقة في عالم الطبيعة فضلا عن رفضها التصديق بكل ما يخضع للحس المباشر، وبما أن مبادئ الدين تقتضي أساسا الإيمان بغير المحسوسات، كان أحرى بالمنهج التجريبي أن يجد في المعرفة غير الحسية مصدرا للنقد والتشكيك بلغ حد التهكّم والسخرية. إلا أن مسارات العلم الحديث أظهرت فارقا بين التجربة العلمية المجردة التي سادت في بداية اللحظة الحديثة للعلم بوصفها لحظة كونية عامة، وبين المذهب التجريبي الذي أحل التجربة أولا كبديل معرفي عن الدين وثانيا كمنهج وحيد للمعرفة التي تتناسب مع عصر التنوير، بينما كان للمذهب المثالي رأي آخر بخصوص تصوره لمفهوم التجربة العلمية وكذا للدين بوصفه مصدرا من مصادر المعرفة، لذلك جنحنا إلى علمني من أعلام المثالية في ألمانية لتقصيّ مصير الدين في التصور الغربي الحديث سواء من حيث كونه مصدرا للمعرفة ومن حيث حضوره في الواقع الاجتماعي، لذلك وقع اختيارنا على كل من الفيلسوف إيمانويل كانط وعالم الاجتماع ماكس فيبر ومنتهين إلى استنتاج حقيقة تلك العلاقة من خلال عمليهما الرئيسيين في الموضوع مكانة العقل في الدين عند كانط ومكانة الدين في المجتمع العقلاني عند فيبر على النحو التالي: لما كان انتفاء الدين من الفكر الإنساني ومن الوجود الاجتماعي متعذّرا فإن ما حدث في الفكر الغربي في علاقته بالدين أمران: أولا أن التجديد الديني في أوروبا الذي حصل سواء نظريا أو عمليا كان متعذّرا نظرا لتعارضه المبدئي مع مفهوم التجريب العقي وذلك لكون النص الديني ونظرا للتحولات التي طرأت عليه صار نصا إنسانيا كغيره من النصوص يفتقد لسمة الشمول والخلود كما تتميز به المعرفة الدينية، وثانيا أن التجريب العلمي ولي يحقق مطلبه المنشود من التقدّم والرقي المادي والحضاري كان لابد له أن يغلق كل منافذ التفكر في الدين من أجل أن ينفصل عنه جذريا من الناحية النظرية وأن يحل محله عمليا.
This article investigates modern science’s claim to act as a substitute for religion. Since the medieval period, experimental science has constituted a clear challenge to religious beliefs and doctrines. The difference was stark between a rational, logical method that seeks truth on the basis of trust in the ideas of the ancients, and an experimental method that relies on observation and scientific experimentation as the exclusive source of truth in the natural world. Experimental science refused to accept any statements or traditions that cannot be submitted to experimentation. Since truth in religion is based on belief in the unseen, it was only a matter of time before experimental science expressed strong doubts and criticism in all truth claims based on the unseen. However, the trajectory of modern science shows a discrepancy between, first, the experimental movement -which imposed itself as an alternative method to religion in seeking truth, and then as the exclusive method that is compatible with the Enlightenment-and, second, the Idealist school which sees both the experimental method and religion as two sources among many other sources of truth. For this reason, this essay focuses on two great thinkers from the German Idealist tradition to enquire about the conception of religion in modern Western thought, both as a source of truth and in terms of its presence in social reality. This essay looks at the philosophical work of Emanuel Kant and the sociological work of Max Weber. This study will try to establish the role that reason plays in religion ,in the work of Kant, and the place that religion plays in the rational society, through the work of Weber. The following points will be made in the conclusion: When it became impossible in Western thought to exclude religion from human thought, two things occurred. First, the religious reforms that were attempted in Europe (theoretically or scientifically) clashed with the concept of experimental science because the religious text lost its sacredness and became a human text. Second, in order for experimental science to achieve the material and civilizational progress that it aspired to, it found it necessary to block all the avenues of rational thought about religion in order to separate itself radically from it and replace it.
Keywords: الفلسفة الإسلامية -- المعتقدات الدينية -- الفكر الغربي -- الإصلاح الديني